Biological and fishery indicators for the small-scale marble crab fishery in Northern Patagonia: recommendations for improving a monitoring program and stock assessment of a data-limited fishery - Hamamé, Madeleine; Aedo, Gustavo; Ortiz, Paula; Olguín, Andrés; Pardo, Luis Miguel (Frontiers in Marine Science, 2024)
Small-scale fisheries have been typically data-limited despite their economic importance for local communities. This is especially true in zones where fishing operations occur in remote areas under harsh weather conditions. Crab fishery in Chile is exclusively artisanal, and marble crab (Metacarcinus edwardsii) has the highest landing records. This species is found in most parts of the coast of Chile, but it is mainly caught in the south of the country (including Patagonia). Fishery management is data-limited, and monitoring has not established the spatial and temporal variability baseline necessary to determine its exploitation status. This fishery is currently evaluated annually under a scheme based on reporting biological and fishery information, primarily from the landing ports and secondarily from fishing grounds. In the present study, we collected data from fishing grounds on board artisanal fishing vessels around 45°S during an annual cycle to establish indicators based on catch per unit effort (above and below minimum legal size), size, sex ratio, and the relationship between weight and size. Our results showed that fishery and biological indicators respond more to seasonal patterns than to expected spatial heterogeneity related to different fishing grounds: proportional stock density (lowest in winter), sex ratio (biased toward males in winter), retained catch (highest in autumn), and released catch (highest in winter), while the average size of the largest 10% of the sample only showed differences between males and females. Additionally, released catch varied according to soak time, which indicates the effectiveness of escape rings incorporated in the traps. These results lead to recommendations related to the current monitoring program, which should include the selection of a limited number of fishing grounds standardized by season and the incorporation of information related to soak time and the presence of escape rings. Finally, this study highlights the importance of on-board scientific monitoring for any fisheries, even those of small scale.